Effect of nitriding on reaction layer of diffusion bonded sialon to AISI 420 martensitic stainless steel - Ibrahim, N.N.M. (Trans Tech Publications Ltd, 2014)
Joining sialon to as-received and nitrided AISI 420 martensitic stainless steels using diffusion bonding is reported in this paper. The samples were joined at 1200Â°C for one hour under uniaxial pressure of 17 MPa in a vacuum (1Ã10-5 Torr). After joining process, the microstructure, interdiffusion of elements, and hardness of the joint were studied. The interdiffusion and reactivity of the elements created the reaction layer. It consisted of interface layer on the sialon side whereas thicker diffusion layer was formed on the steel side. Thinner reaction layers were observed in joining sialon to nitrided steels compared to joining sialon to as-received steel due to less reactivity between the joined materials. However, more precipitates such as carbides were formed in the parent steel with longer nitriding time. Gaps were formed between the diffusion layer and the parent steel but the interfacial bonds were strong since no cracking occurred on the samples. Since the reaction layer had intermediate hardness, it contributed to the jointâs ductility that reduced the effect of thermal expansion mismatch between the joined materials by acting as a shock absorbing zone. Â© (2014) Trans Tech Publications, Switzerland.